Ṣūratu Mar’ati fī Qiṣṣati Maryama fī al Qur’āni al Karīmi (Dirāsatu al Adabiyyati al Niswiyyati) - Nabila, Jihan; Yusuf, muhammad (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
The study of feminism is a literarytradition that leads tokan fokus analisis to female. One of the focuses of the study of feminism is the image of women. In the Qur'an there are many verses that tell about women, there is even one surah that tells the female character specifically, surah Maryam. The purpose of this research is to describe the image of women in the story of Maryam in the Quran including psychic imagery and social imagery. The data collection method that library studies use. The method of data analysis used is a qualitative descriptive method. The subjects in this study are the text of surah Ali Imran, surah Maryam, and surah At Tahrim in the Qur'an. The result of this study is a psychic image ofa woman in the storyof Maryam in the Qur'an consisting of 1)a sincereperson,(2)a devout worshipter,(4)a worried person,(4)a fearful person,(5)a man who is inflicted in pain, and(6)a man who guards honor. The social image of women in the story of Maryamin the Qur'an in the family and community consists of (1)a nephew, (2a) mother, ( 3a child, (4) a sister, (5) a weak man rather than a man in worship (6) an exiled person, (7) a contested person, (8) an accused person, and (9) a man who is given to serve. Based on the analysis of the above imagery found gender injustice contained in this study in the form of stereotypes and violence